2013
DOI: 10.1260/1369-4332.16.10.1671
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Collapse Assessment of RC Structures under Instantaneous and Gradual Removal of Columns

Abstract: The subject of progressive collapse assessment in RC structures has been concerned in various studies. In contrast, most of these studies have attended to a scenario in which an instantaneous removal of a column due to unexpected impact or explosion has occurred. The present study addresses progressive collapse in RC structures resulting from both instantaneous and gradual removal of columns. The scenario for a gradual removal is the result of slow decreasing strength due to fire propagation in a specific zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Kwasniewski (2010) also developed a detailed 3D model to evaluate the progressive collapse resistance of an eight-storey steel frame in the Cardington Fire Test. The structural responses of RC structures under instantaneous and gradual removal of columns were also compared by Rahai et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kwasniewski (2010) also developed a detailed 3D model to evaluate the progressive collapse resistance of an eight-storey steel frame in the Cardington Fire Test. The structural responses of RC structures under instantaneous and gradual removal of columns were also compared by Rahai et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated that collapse mechanism of composite frame consisted of six stages including elastic, elastic-plastic, arch, plastic, transient and catenary stages; and the catenary action could enhance the resistance of rigid composite frame evidently. Rahai et al [10] addressed progressive collapse in a five-story reinforced concrete building model resulting from gradual removal of columns due to fire propagation in a specific zone of structure and compared the results with the findings in the scenario of instantaneous removal of column. Xiao et al [11] conducted three tests of a three-bay x three-bay, three-story and half-scale RC frame following a series of sudden column removals.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the sudden column loss is a useful design scenario for assessing structural robustness and may result in an upper bound of the deformation under blast events. Rahai et al (2013) compared the instantaneous and gradual column-removal responses of an RC structure and revealed that the former induced higher stress and deformation demand on the structure. So far, most studies regarding the rise-time effect were mainly carried out with dynamic time-history analyses.…”
Section: Introductionmentioning
confidence: 99%